2019
DOI: 10.1186/s12870-019-1747-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of HvXYN1 associated with endoxylanase activity and TAX content in barley (Hordeum vulgare L.)

Abstract: Background: Endo-β-1,4-xylanase1 (EA), the key endoxylanase in plants, is involved in the degradation of arabinoxylan during grain germination. In barley (Hordeum vulgare L.), one gene (HvXYN-1) that encode a endo-beta-1,4-xylanase, has been cloned. However, the single nucleotide polymorphisms (SNPs) that affect the endoxylanase activity and total arabinoxylan (TAX) content have yet to be characterized. The investigation of genetic variation in HvXYN1 may facilitate a better understanding of the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…In this study, 481 SNPs were identified from 60 HvmTERF genes across 220 wild and landrace barley accessions. The SNPs were distributed unevenly along the genomic sequence, including a total of 292 exon and 44 intron variations, which was consistent with a previous study showing higher polymorphism of SNPs in exon regions than in intron regions (Lu et al, 2019) but opposite to observations in other studies (Uçarli et al, 2016;Xia et al, 2017). The PCA, admixture, and phylogenetic analyses clearly divided all the accessions into landraces and wild barley accessions and further distinguished them geographically.…”
Section: Nucleotide Diversity Analysis Indicated That Hvmterf Genes Experienced a Weak Bottleneck During Barley Domesticationsupporting
confidence: 87%
“…In this study, 481 SNPs were identified from 60 HvmTERF genes across 220 wild and landrace barley accessions. The SNPs were distributed unevenly along the genomic sequence, including a total of 292 exon and 44 intron variations, which was consistent with a previous study showing higher polymorphism of SNPs in exon regions than in intron regions (Lu et al, 2019) but opposite to observations in other studies (Uçarli et al, 2016;Xia et al, 2017). The PCA, admixture, and phylogenetic analyses clearly divided all the accessions into landraces and wild barley accessions and further distinguished them geographically.…”
Section: Nucleotide Diversity Analysis Indicated That Hvmterf Genes Experienced a Weak Bottleneck During Barley Domesticationsupporting
confidence: 87%
“…This can be explained considering that the total AX content may be greatly affected by environmental factors; for example, water deficiency could increase AX content. 3 Nevertheless, the factorial analysis demonstrated that the influence of year on the total AX content was not statistically significant.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Recently the gene HvXYN-1 that encode a endobeta-1,4-xylanase (EA) in barley was studied to understand the relationship between AX content and EA. These authors found two variants that significantly ( P < 0.0001) affected EA activity and that could be applied as DNA markers in breeding programs to improve barley quality . Approximately 50% of the AX in barley is found in the husk and pericarp .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations